Dinamika Pendidikan Kewarganegaraan - Siti Fatimah; Diana Rizky; Neni Angriani (PT. Willy Print Art, 2025)
The implementation of Civic Education (PKn) learning which is carried out from elementary school to higher education still requires improvement efforts until now, because the character problems of the younger generation are getting more complex, input from the results of the analysis is needed to provide solutions to these problems. The purpose of writing this article is to analyze the dynamics of the implementation of PKn learning at the age of our beloved country which is 75 years old. The method used in this article is a literature study, by analyzing studies on civic education and then drawing conclusions. The results of this article are that efforts to improve the quality of PKn learning still need to be studied. One of the recommendations for improvement is first, to provide role models for students, both role models at school by teachers and role models by parents in the family environment. Second, increase teacher creativity in learning starting from learning innovation by implementing various learning models, methods and media. Third, improve institutions, both teacher organizations such as the Subject Teacher Conference (MGMP) and associations from universities.